Comparison of Female Genital Tract Cytokine and Microbiota Signatures Induced by Initiation of Intramuscular DMPA and NET-EN Hormonal Contraceptives - a Prospective Cohort Analysis - Dabee, Smritee; Tanko, Ramla F.; Brown, Bryan P.; Bunjun, Rubina; Balle, Christina; Feng, Colin; Konstantinus, Iyaloo N.; Jaumdally, Shameem Z.; Onono, Maricianah; Nair, Gonasagrie; Palanee-Phillips, Thesla; Gill, Katherine; et al. (Frontiers in Immunology, 2021)
Background Cervicovaginal inflammation, bacterial microbiota and hormonal contraceptives all influence sexual and reproductive health. To date, the effects of intramuscular depo-medroxyprogesterone acetate (DMPA-IM) versus injectable norethisterone enanthate (NET-EN) on vaginal microbiota or cytokines have not been compared back-to-back, although in-vitro data suggest that DMPA-IM and NET-EN have different pharmacokinetic and biologic activities. This study aimed at comparing the effects of DMPA-IM versus NET-EN initiation on cervicovaginal cytokines and microbiota in women at high risk for sexually transmitted infections (STIs) assigned to the respective contraceptives. Methods We collected socio-demographic characteristics and vaginal samples from women initiating DMPA-IM (ECHO Trial; n = 53) and NET-EN (UChoose Trial; n = 44) at baseline and after two consecutive injections to assess cytokine concentrations by Luminex, vaginal microbiota by 16S rRNA gene sequencing, STIs, bacterial vaginosis (BV) and candidiasis. Results Cytokine concentrations did not change significantly after initiating DMPA-IM or NET-EN, although NET-EN versus DMPA-IM-associated profiles were distinct. While the abundance of bacterial taxa associated with optimal and non-optimal microbiota fluctuated with DMPA-IM use, overall community composition did not significantly change with either contraceptive. HSV-2 serology, chlamydial infection, gonorrhoea and candidiasis did not influence the associations between contraceptive type and cervicovaginal cytokines or microbiota. Conclusions Both DMPA-IM and NET-EN use did not lead to broad inflammatory or microbiota changes in the female genital tract of sub-Saharan African women. This suggests that NET-EN is likely a viable option for contraception in African women at high risk of BV and STIs.